2021
DOI: 10.1177/1055665621996107
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Treatment Outcomes of Absorbable Sutures, Nonabsorbable Sutures, and Tissue Adhesives in Cleft Lip Repair: A Systematic Review

Abstract: Objectives: To examine the literature and synthesize the available reports for the best possible option between absorbable, nonabsorbable, and tissue adhesives in cleft lip skin closure. Design: We conducted systematic searches for randomized controlled trials and controlled clinical trials in PubMed, Cochrane, Ovid Medline, and OpenGrey databases. Identified studies were retrieved and assessed for eligibility. All statistical analyses were done with Revman, version 5.4. Interventions: The intervention conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 29 publications
(112 reference statements)
0
19
0
Order By: Relevance
“…73 Nonabsorbable sutures have been described as outperforming absorbable sutures in tensile strength, resulting in better tissue approximation, and thus improved would healing. 74 Regarding cleft lip repair, Egbunah et al 6 found nonabsorbable sutures to provide better wound healing cosmesis conditions, with, however, more postoperative complications when compared with absorbable sutures. Others found a tissue glue (Dermabond) to perform similarly to 6-0 Monocryl suture in terms of parentreported and surgeon-reported cosmetic satisfaction and overall rate of complications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…73 Nonabsorbable sutures have been described as outperforming absorbable sutures in tensile strength, resulting in better tissue approximation, and thus improved would healing. 74 Regarding cleft lip repair, Egbunah et al 6 found nonabsorbable sutures to provide better wound healing cosmesis conditions, with, however, more postoperative complications when compared with absorbable sutures. Others found a tissue glue (Dermabond) to perform similarly to 6-0 Monocryl suture in terms of parentreported and surgeon-reported cosmetic satisfaction and overall rate of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although roughly half of all included studies related to patient pain and analgesia, others focused on topics ranging from the utility of perioperative antibiotics, risk factor analysis, suture materials, inpatient versus outpatient surgical outcomes, and timing of the surgical procedure on complication rates. 6,41,50,56,63,64 Such a comprehensive approach to identifying PS and QI strategies allows for more impactful and contextual practice recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations